A Phenomenological Study on Sexuality Education for Children and Adolescents with Autism Spectrum Disorder in Jakarta - Fitria Ayuningtyas; Jude William R Genilo; Drina Intyaswati; Irpan Ripai Sutowo; Anter Venus (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
This research is motivated by the researchers' concern about children,  especially adolescents with autism. Autism is not a mental illness but it is a disorder that affects  the brain, causing it to not function properly. This can be seen in the behavior of children with autism. The purpose of this research is  to find out the experiences of parents of  children and adolescents with autism spectrum disorder. This research uses a qualitative research design with a research approach to phenomenology. The result of this research showed that sex knowledge of children with autism spectrum disorder is still limited to  knowledge of differences between male and female sexes. They obtained sexual knowledge education from schools, while some received it from teachers, therapists, and parents. The level of independence is high. Sexual prohibition is important to give children the knowhow to maintain behavior towards the opposite sex. To improve the sexual health education of parents who have children with autism spectrum disorder, they can attend sexual education seminars.